Comparative Study of Career Adaptability of Grade XI Students of Senior High School and Madrasah Aliyah in Wajo Regency - Subhan, Nurul Izzah; Wangid, Muhammad Nur; Wulandari, Annisa Silvia; Jacub, Rahmifanti R.; Arifudin, Moch. (Proceeding International Conference on Religion, Science and Education, 2025)
This study aims to examine the differences in the level of career adaptability between Senior High School (SMA) and Madrasah Aliyah (MA) students in Wajo Regency. Career adaptability is an important aspect in preparing students to face the challenges of an increasingly dynamic world of work, including the ability to adjust to career changes and take advantage of existing opportunities. Given the different background characteristics of the educational environment, this study examines whether there are significant differences in the level of career adaptability of students from the two types of schools. The method used in this study is a quantitative approach with the Mann-Whitney test as a data analysis technique. The results showed that the difference in career adaptability between SMA and MA students was not statistically significant, with a p value of 0.536 (p > 0.05) with the mean rank of career adaptability of SMA students being 60.43, while MA students were 56.57. This shows that although high school and middle school students come from different educational backgrounds, their levels of career adaptability are relatively similar. This finding provides an interesting insight into the homogeneity of career adaptability levels in two types of educational institutions that have been considered to have fundamental differences in terms of curriculum. The implications of this study emphasize the importance of a holistic and equitable career guidance approach in all types of schools, both senior high schools and senior high schools, to prepare students for a career future that is likely to change due to rapid developments in the modern era. This study makes a significant contribution to the career guidance literature by opening up further discussion on the factors that influence similar levels of career adaptability among students. Thus, the results of this study are expected to serve as a foothold for the development of more effective career guidance policies and programs in various educational institutions.